2021
DOI: 10.1038/s41375-021-01192-7
|View full text |Cite
|
Sign up to set email alerts
|

Dactinomycin induces complete remission associated with nucleolar stress response in relapsed/refractory NPM1-mutated AML

Abstract: Acute myeloid leukemia (AML) with mutated NPM1 accounts for one-third of newly diagnosed AML. Despite recent advances, treatment of relapsed/refractory NPM1-mutated AML remains challenging, with the majority of patients eventually dying due to disease progression. Moreover, the prognosis is particularly poor in elderly and unfit patients, mainly because they cannot receive intensive treatment. Therefore, alternative treatment strategies are needed. Dactinomycin is a low-cost chemotherapeutic agent, which has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 42 publications
3
25
0
Order By: Relevance
“…Recent clinical studies have shown that the rDNA transcriptional inhibitor ActD (Dactinomycin®) can induce complete remissions and even cure some refractory/relapsed NPM1c-AML patients as a single agent (21)(22)(23). Transcriptional inhibition of rDNA genes by ActD induces nucleolar segregation and activates TP53 through ribosomal checkpoint activation upon MDM2-L5/L11 complex formation (34).…”
Section: Actinomycin D Targets Mitochondria and Promotes Superoxide Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Recent clinical studies have shown that the rDNA transcriptional inhibitor ActD (Dactinomycin®) can induce complete remissions and even cure some refractory/relapsed NPM1c-AML patients as a single agent (21)(22)(23). Transcriptional inhibition of rDNA genes by ActD induces nucleolar segregation and activates TP53 through ribosomal checkpoint activation upon MDM2-L5/L11 complex formation (34).…”
Section: Actinomycin D Targets Mitochondria and Promotes Superoxide Responsementioning
confidence: 99%
“…Here, we demonstrate that NPM1c blunts PML NB-biogenesis and weakens mitochondrial fitness. Actinomycin D (ActD), a drug with established clinical activity in therapy-resistant NPM1c-AML (21)(22)(23), induces acute mitochondrial stress, ROS production, restoration of PML NBs, and senescence, contributing to its therapeutic efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Deep investigations on the effects of dactinomycin in cells carrying NPM1 mutations lead to the demonstration that expression of NPM1 mutant lowers the threshold for stress-induced cell death (Gionfriddo et al, 2021), providing an explanation for its clinical activity in NPM1-mutated AML, reported by the same group of researchers. Moreover, with the collaboration of the group coordinated by Prof. Hugues de Thè (Collège de France, INSERM, Paris), it was found that NPM1 mutant impairs vital cellular functions, specifically mitochondrial fitness and function of the PML tumour suppressor, favouring the action of dactinomycin.…”
Section: Screening-based Approachmentioning
confidence: 89%
“…Careful monitoring of the correlation between NPM1-mutated transcripts MRD and specific T-cell responses against NPM1-mutated peptides, easily evaluable in PB samples, may provide relevant prognostic information [19]. Beyond novel agents either targeting abnormal cell transport of NPM1-mutated protein, such as XPO1 inhibitors, or targeting HOX expression, namely the menin-MLL inhibitors MI3454 and VTP-50469, or triggering nucleolar stress, such as dactinomycin, which have shown anti-leukemic activity in pre-clinical models and have started to be investigated in humans, immunotherapeutic approaches targeting NPM1-mutated protein processed and presented by HLA system on AML cell surface could represent an effective treatment option, at least in some distinct disease phases [7,91,92]. Due to diverse bioinformatic instruments and in vitro/ex vivo immunological platforms employed, investigators identified different epitopes from NPM1-mutated protein showing the potentially highest immunogenicity, as detailed in Table 1 [4,15,16,[18][19][20][21]25].…”
Section: Discussionmentioning
confidence: 99%